1986
DOI: 10.2527/jas1986.624958x
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal Circumference in Yearling Hereford Bulls: Adjustment Factors, Heritabilities and Genetic, Environmental and Phenotypic Relationships with Growth Traits

Abstract: Field data on 4,233 yearling Hereford bulls were analyzed using fixed and mixed model least-squares procedures to examine factors affecting scrotal circumference; determine appropriate adjustment factors; and study genetic, environmental and phenotypic relationships among scrotal circumference and growth traits. Scrotal circumference was affected by postweaning feed level; contemporary group/feed level; age of dam; and covariates age, weight and height. Of the three covariates, weight had the greatest effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
53
6
13

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 7 publications
17
53
6
13
Order By: Relevance
“…Among the independent variables, BW had the lowest associations with final WT, SC and HHT and, therefore, was least useful in predicting the dependent variables. The low correlation between SC and BW in young beef bulls is in agreement with the genetic correlation estimate of 0.18 as reported by Bourdon and Brinks (1986). Brinks (1994) reported that growth of bulls from birth to yearling was positively correlated with SC, but BW had low association with SC.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Among the independent variables, BW had the lowest associations with final WT, SC and HHT and, therefore, was least useful in predicting the dependent variables. The low correlation between SC and BW in young beef bulls is in agreement with the genetic correlation estimate of 0.18 as reported by Bourdon and Brinks (1986). Brinks (1994) reported that growth of bulls from birth to yearling was positively correlated with SC, but BW had low association with SC.…”
Section: Resultssupporting
confidence: 90%
“…The equations explained 92 and 67 per cent of variation in final feedlot weight and scrotal circumference, respectively. These results confirmed the evidence that growth of bulls from birth to yearling age and testicular development were highly correlated, at least in beef bulls which had undergone postweaning performance testing (Bourdon and Brinks, 1986). Farid and Makarechian (1983) estimated that 60-75 percent of variation in SC (R2) could be accounted for changes in body weight during preweaning and 145-d feedlot test periods in beef bulls.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations